IMF Staff papers : Volume 33 No. 2. (IMF Staff Papers; IMF Staff Papers, 1986)
WILLIAM. white, who joined the International Monetary Fund in 1948, spent his entire professional life in the Research Department. Present and past staff members, many of whom benefited from his advice, have asked that his contribution-to the work of the Fund should receive recognition in Staff Papers. This appreciation draws on excerpts from written recollections of some of his colleagues.